\(γ e^{-} → h e^{-}\) Collision in Randall - Sundrum Model - Giang, Bui Thi Ha; Thuy, Dao Thi Le (Communications in Physics, 2015)
We consider the Randall - Sundrum model, which solves the Higgs hierarchy problem. In this paper, we have calculated the cross - section of the \(γ e^{-} → h e^{-}\) process with the polarization of the electron beams. Based on the results, we show that the reaction can give observable cross - section in future accelerators at the high degree of polarization